How AI can Change/Improve/Influence Music Composition, Performance and Education: Three Case Studies - Harun Zulić (INSAM)
The use of artificial intelligence in science is happening more and more frequently, and often artificial intelligence can be seen in different approaches to creating music and art. In this paper, I will present some of the research that has been carried out, which involve the use of artificial intelligence in the field of composition, performance, and music education. The main focus in the field of composition will be on AIVA – the first virtual composer created with artificial intelligence, which is registered with an author’s rights society. In the field of performance, we’ll mostly talk about Yamaha's experiment where the world-renowned dancer Kaiji Moriyama controls a piano with his body movements, and in the context of education, this paper reviews some of the possibilities in a variety of artificial intelligence approaches to music education. Lastly, I will conclude the paper by presenting the direction of and possible future for the use of artificial intelligence in music.